Implementing Group Investigation (GI) Learning Method to improve the Students’ Learning Achievement of Senior High School - Megawati, Nurcaya (International Journal of Education Research and Development, 2023)
The purpose of this study is to use the group investigation (GI) learning model to increase the learning success of class X Language SMA Negeri 2 Rejang Lebong on the subject of consumption and investment. This study is called classroom action research (CAR). This study was carried out at SMA Negeri 2 Rejang Lebong. For the 2018-2019 academic year, the research subjects were 28 class X Language students. This study was carried out during March and April of 2019. In this study, three approaches were employed to collect data: the test method, the observation method, and the documentation method. Following the collection of data, it is analyzed using a descriptive percentage approach. According to the findings of this study, student success climbed from 21.42% to 71.43% in Cycle I and then again to 85.19% in Cycle II. This rise has an impact on the rise in learning achievement. This is reflected in the rising average value of students. The average student score climbed from 67.71 with a percentage of student learning completeness of 21.42% in the pre-cycle to 77.43 with a percentage of student learning completeness of 71.43% in cycle I and 85.44 with an 85.19% completeness in cycle II. As a result, it is possible to conclude that using the group inquiry (GI) learning approach can increase student success in economic courses.